1997
DOI: 10.1179/sur.1997.13.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anodised coatings on fatigue crack growth rates in aluminium alloy

Abstract: This paper reports the findings of fatigue crack growth measurements on a 2014 aluminium alloy that had been anodised using the recently developed boric acidsulphuric acid process. The results demonstrate that fatigue crack growth rates in this alloy can be markedly enhanced by the presence of a thin anodic oxide film. This enhancement can be explained in terms of reduced plasticity induced closure assisted by surface cracking of the brittle oxide film ahead of the propagating fatigue crack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Camargo et al [9] have shown that internal tensile residual stresses, as a consequence of anodization on 7050-T7451, is one of the reasons for degrading stress-life fatigue performance of the substrate. Study by Cree and Weidmann [10] on anodized 2024 alloy has demonstrated that fatigue crack growth rate can be significantly enhanced in the presence of thin anodic film. They explained the increased growth rate in terms of possible tensile residual stress in film and its inherent higher modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Camargo et al [9] have shown that internal tensile residual stresses, as a consequence of anodization on 7050-T7451, is one of the reasons for degrading stress-life fatigue performance of the substrate. Study by Cree and Weidmann [10] on anodized 2024 alloy has demonstrated that fatigue crack growth rate can be significantly enhanced in the presence of thin anodic film. They explained the increased growth rate in terms of possible tensile residual stress in film and its inherent higher modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Anodizing is well-known electrolytic process that produces controlled columnar growth of amorphous aluminium oxide on the surface of aluminium alloys as documented in ASM Handbook (1998). Despite the benefits obtained by anodizing in terms of cor-rosion resistance, it has been shown (Cree and Weidmann, 1997) and (ESDU document 87026, 1994) that anodizing has adverse effect on fatigue life of aluminium alloys. It is generally accepted that this reduction in fatigue life is directly attributed to the brittle and porous nature of oxide layer and tensile residual stress induced during anodizing process as demonstrated by Camargo and Voorwald (2007) for alloy 7050-T7451 and Cirik and Genel (2008) for alloy 7075-T6.…”
Section: Introductionmentioning
confidence: 99%
“…According to Lockheed Martin surface treatment methods [8], the sulfuric acid process Type II had been used for the anodized materials being investigated in this study. Unfortunately, sulfuric acid anodizing has been reported to be more detrimental than the chromic acid process in terms of fatigue performance [16].…”
Section: Discussionmentioning
confidence: 99%
“…Cladding and anodizing have previously been observed to have deleterious effects on fatigue performance [16,17]. A clad layer has a much lower yield stress than the substrate material.…”
Section: Discussionmentioning
confidence: 99%